2005
DOI: 10.1167/5.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Long-wavelength adaptation reveals slow, spectrally opponent inputs to the human luminance pathway

Abstract: In addition to its expected fast, additive L- and M-cone inputs (L + M), the luminance pathway has slow, spectrally opponent inputs. We have previously shown that on long-wavelength fields, the dominant slow signals change from L-M at moderate intensity levels to M-L signals at high. Here, we focus on the transition between them, which we find is marked by substantial changes in temporal phase delay, and by large and unexpected shifts in flicker spectral sensitivity. At moderate temporal frequencies, counter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
4
16
0
Order By: Relevance
“…Consistent with this view, three recent, meticulous psychophysical studies revealed strong, non-linear interactions between the human luminance channel and chromatic opponent channels [44][46], thus providing the necessary pre-cortical substrate for the correspondence between colour brightness and V1 activity reported here. While arguing for a potential retinal locus for these interactions, these authors also highlighted previous studies showing colour-luminance interactions at the level of single V1 cells [47][49].…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with this view, three recent, meticulous psychophysical studies revealed strong, non-linear interactions between the human luminance channel and chromatic opponent channels [44][46], thus providing the necessary pre-cortical substrate for the correspondence between colour brightness and V1 activity reported here. While arguing for a potential retinal locus for these interactions, these authors also highlighted previous studies showing colour-luminance interactions at the level of single V1 cells [47][49].…”
Section: Discussionsupporting
confidence: 84%
“…The inverted and delayed phase delays shown here are not confined to S-cone signals. M-cone phase delays with similar phase characteristics have been reported before under comparable conditions (Stockman & Plummer, 2005a, 2005b. Figure 7 shows such M-cone phase delays measured on the 610-nm background fields decreasing in steps from 10.41 log 10 quanta s j1 deg j2 for KR and from 9.39 log 10 quanta s j1 deg j2 for WL.…”
Section: Sluggish Inverted M-cone Signalssupporting
confidence: 79%
“…Indeed, similarly large delays are found in many other experiments using L-, M-, and Scone flicker using similarly sized fields (Stockman, Montag, & Plummer, 2006;Stockman & Plummer, 2005a, 2005bStockman, Plummer, & Montag, 2005;Stockman, Sharpe, Zrenner, & Nordby, 1991;Stromeyer et al, 2000). This is a topic we will return to in future papers.…”
Section: Determination Of the Late Filter Shapessupporting
confidence: 64%